Study of Profile of Motor Vehicle Accidents in Thiruvanmiyur Traffic Police Station (Indian Journal of Forensic Medicine & Toxicology, 2020)
Accidents are an intentional act which is not a voluntary act done by the people. Accidents, tragically, are notoften due to ignorance, but are due to carelessness, thoughtlessness and over confidence [1]. Human, vehicleand environmental factors play roles before, during and after a trauma event. Accidents, therefore, can bestudied in terms of agent, host and environmental factors and epidemiologically classified into time, placeand nature of injury.